Analisis Kualitatif pada Situs Website Forum Diskusi Menggunakan Usability Testing (Studi Kasus: www.dictio.id) - Tony Effendi; Himawat Aryadita; Adam Hendra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Website dictio is a community to share, learn, discuss intelligently, critically, and courteously through online media. Based on the interviews to stakeholders of dictio parties, it is found that dictio website has a problem, which is the use of features contained in the website dictio like the use of language. The purpose of this usability testing is to measure the quality level of the website and it can be a material improvement proposal for dictio developer team. Data collection used in this research is by using questionnaires, giving test assignments, and conducting interviews after testing dictio website. From the test results, it can be obtained that the usability value of the Effectiveness criteria is 78%, then 75% for usability level value of Usefulness, 31% for usability level value of Satisfaction, and then 75% for usability level value of Efficiency. In the use of language in dictio website, the result of the interview showed that partisipants prefer using two languages, namely Indonesian and English, and for like lending features, partisipants prefer using thumb up. Hereafter, we suggest improving usability criteria in each category. There are two recommendations improvement for usability criteria value of Effectiveness, one recommendation improvement for usability criteria value of Usefulness, five recommendations improvement for usability criteria level of Satisfaction, and last two recommendations improvement for usability criteria Efficiency.